The repercussions of achieving economic growth by relying on international financial markets - Abdellah Kellouche; Rim Benmostefa (Advanced Research in Economics and Business Strategy Journal)
The international financial markets are considered one of the modern topics that have attracted public opinion recently, as the importance of the study appears in being the most important frameworks and mechanisms that the major economic countries are looking for in light of the division and specialization in production and the presence of national currencies, in addition to considering it the basis of foreign trade. The study aimed to highlight the development of the concept of These markets over time from the concept of the market as a geographical space like other specialized markets until it reached a comprehensive and recognized academic concept as geographically undefined mechanisms and frameworks aimed at achieving a strategic goal represented in meeting the needs of countries with financial deficits and achieving the benefits of surplus countries. The results of the study concluded that it is necessary to pay attention to international financial markets in order to create integrated international commercial, monetary and financial relations for financial decisions in institutions at the local and international levels and to achieve economic growth that most countries of the world aim to achieve economic stability and social welfare.